1999
DOI: 10.1177/009164719902700105
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Moral, Religious, and Identity Development in a Christian Liberal Arts Environment

Abstract: many and diverse, and students looking for a post-high school education have a plethora of choices. One of those choices is to pursue a college degree in a faith-based college or university. Christian colleges and universities provide opportunities for students to pursue traditional courses of study, as well as religious and ministry options, in a milieu that is consistent with their religious beliefs. Through required courses, chapel programs, ministry opportunities, the integration of faith into AUTHORS FOST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 17 publications
2
16
0
1
Order By: Relevance
“…Across these studies, students' use of conventional level reasoning decreased during college, and their use of postconventional moral reasoning increased (Burwell, Butman, and Van Wicklin, 1992;Foster and LaForce, 1999;King and Kitchener, 1994;King, Kitchener, and Wood, 1985;Mentkowski and Strait, 1983;Rest, 1979b;Shaver, 1985Shaver, , 1987Whiteley, 1982), offering evidence that collegiate experiences promote the development of moral reasoning among undergraduate students. The first of these are longitudinal studies, which are essential for the validation of any developmental model.…”
Section: Effects Of Participation In Higher Education On Moral Reasoningmentioning
confidence: 96%
“…Across these studies, students' use of conventional level reasoning decreased during college, and their use of postconventional moral reasoning increased (Burwell, Butman, and Van Wicklin, 1992;Foster and LaForce, 1999;King and Kitchener, 1994;King, Kitchener, and Wood, 1985;Mentkowski and Strait, 1983;Rest, 1979b;Shaver, 1985Shaver, , 1987Whiteley, 1982), offering evidence that collegiate experiences promote the development of moral reasoning among undergraduate students. The first of these are longitudinal studies, which are essential for the validation of any developmental model.…”
Section: Effects Of Participation In Higher Education On Moral Reasoningmentioning
confidence: 96%
“…For instance, relating empathetically with others or learning to help others in need may stimulate values of respecting all individuals despite their diverse backgrounds and characteristics. Foster and LaForce (1999) found that students who persisted in Christian higher education colleges across 4 years grew significantly in their moral reasoning, their personal identity changed from a diffuse to more committed style, compared to students who did not continue at their faith-based schools. This study suggested that faith-based higher education institutions might transmit values and enable students to achieve ethical and moral development that reflects the institution's mission statement.…”
Section: The Current Project: Assessing Institutional Mission and Valuesmentioning
confidence: 98%
“…In a longitudinal study conducted by Foster and LaForce (1999), students were able to most benefit from the Christian college experience when they actively engaged in attempting to form their identity. Lee (2002) also noted that students who were able to use self as agent in their college experience were most successful in forming identity.…”
Section: Active Searchingmentioning
confidence: 99%